Evaluasi Pembelajaran Pramuka dengan Penerapan K13 di SDN 2 Bagik Payung - Yuliana, Elfa; Hartini, Hartini (Lembaga Bale Literasi, 2024)
This research aims to find out what aspects are used in scout learning, to find out the methods used in scout learning, to find out the form of evaluation used in scout learning so that scouting education is achieved or implemented at SDN 2 Bagik Payung. The scouting method is a reference used in scouting education that is interesting, challenging and fun so that learning objectives are achieved. Scouting methods are carried out holistically and are not separated in their application. The results of the research found that the method used for scout learning at SDN 2 Bagik Payung was learning while practicing. This method is used as a reference for use in scouting education that is interesting, challenging and fun so that learning objectives are achieved.